Morphological detection of charcoal rot in soybean and corn in Misiones, Argentina - Lavilla, M.; De Lucía, A.; Heck, M.; Fariza, S. (Agronomía Mesoamericana, 2023)
Introduction. Charcoal rot caused by Macrophomina phaseolina is a pathogen that survives in the soil through microsclerotia (Sclerotium bataticola stage). This pathogen affects different crops, among which soybeans (Glycine max L. Merrill) and corn (Zea mays L.) stand out due to their importance in Argentina. Objetive. To demonstrate that the cause of the deaths of soybean and corn plants in years of drought in the province of Misiones is charcoal rot. Materials and methods. Samples were collected from different locations in the province of Misiones, Argentina during February 2022. Through naked eye observation of diseased plants and with the help of stereoscopic and optical microscopy, the identity of the pathogen present was determined. Results. The presence of microsclerotia compatible with S. bataticola as the causal agent of charcoal rot was detected in corn and soybean samples in all samples from the province of Misiones. Conclusion. Charcoal rot caused by M. phaseolina is present in soybean and corn crops in the province of Misiones, Argentina.